(untitled) (Journal of the College of Education for Women, 2019)
Summed up the idea of this research in an attempt to find the establishment of the knowledge convergence to show the features of verbal acts that occurred a prime location in the lesson deliberative theory book unique contract ( IbnAbdRabbaAndalusian ) to prove that Arabic was the old literary studies included many of the features of this theory in both theoretical and practical